(Liquid + liquid) extraction of 2-propanol from aqueous solutions using extracting agents ethyl butyrate and n-pentyl acetate at three temperatures. (May 2020) - Peng, Wenfeng; Li, Hongling; Zhang, Quanzhou; Chen, Yao
Highlights: LLE data at three temperatures for (water + 2-propanol + ethyl butyrate or n-pentyl acetate) systems were determined. The LLE data were correlated by using the extended and modified UNIQUAC models. The reliability of the experimental LLE data was verified by the Hand and Bachman equations. Distribution coefficients and separation factors were compared with those of other extracting agents from the literatures. Extraction performance of ethyl butyrate and n-pentyl acetate to extract 2-propanol from aqueous solutions was confirmed. Abstract: (Liquid + liquid) equilibrium (LLE) data were determined for two ternary systems of (water + 2-propanol + ethyl butyrate) and (water + 2-propanol + n-pentyl acetate) at T  = (293.15, 303.15 and 313.15) K under atmospheric pressure. The experimental data were correlated by the thermodynamic modified UNIQUAC and extended UNIQUAC models. The consistency of the experimental LLE data was further ascertained by applying Hand and Bachman equations. The extraction capability of ethyl butyrate and n-pentyl acetate was estimated by distribution coefficients and separation factors. The extraction efficiencies of ethyl butyrate and n-pentyl acetate were compared with those of other extraction agents such as isobutyl acetate, butyl acetate, butyl propionate and sec-butyl acetate. And extraction performance of ethyl butyrate and n-pentyl acetate in the extraction of 2-propanol from 2-propanol-water solutions was confirmed.